The movement of motion-defined contours can bias perceived position - Durant, Szonya (The Royal Society, 2009)
Illusory position shifts induced by motion suggest that motion processing can interfere with perceived position. This may be because accurate position representation is lost during successive visual processing steps. We found that complex motion patterns, which can only be extracted at a global level by pooling and segmenting local motion signals and integrating over time, can influence perceived position. We used motion-defined Gabor patterns containing motion-defined boundaries, which themselves moved over time. This ‘motion-defined motion’ induced position biases of up to 0.5°, much larger than has been found with luminance-defined motion. The size of the shift correlated with how detectable the motion-defined motion direction was, suggesting that the amount of bias increased with the magnitude of this complex directional signal. However, positional shifts did occur even when participants were not aware of the direction of the motion-defined motion. The size of the perceptual position shift was greatly reduced when the position judgement was made relative to the location of a static luminance-defined square, but not eliminated. These results suggest that motion-induced position shifts are a result of general mechanisms matching dynamic object properties with spatial location.